The Occupy Wall Street movement as a 'space of profanation' - Rinaldi, Alberto (AUC Knowledge Fountain, 2012)
Born in a crucial historical moment - the decennial of 9/11, and more than ten years after the anti-globalization movement of Seattle - the Occupy Wall Street movement (OWS) has awaken again protest and dissent, for the first time at the heart of the largest financial centre of world. More â mature' than its predecessor and also increasingly more encompassing, this movement is presently working as a sort of â sounding board' of protest and dissent, finding its inspiration in the Arab Spring, the Spanish indignados, and in all other forms of systemic protests that have flared around the world since the 2008 global financial crisis. In the present paper, I will argue that the Occupy Wall Street movement has opened a new space for resistance and, drawing on Giorgio Agamben's concept of profanity, I will call the Occupy movement a â space of profanation.' I will therefore argue that this kind of profanation represents one of the best possible acts of resistance for the present time, as we live in a hyper-legalized age, where the narratives of neoliberal economics, security, crisis and human rights tend to monopolize the legal-political debate almost worldwide, and thus tend to close other potential spaces for resistance and rights-demand. As a matter of fact, the tremendous shift to no-demand, the diversity of the movement, its being characterized by decentralization and its anti-elitarian nature, with a focus on sharing, community and a clear tendency to 'inefficiency,' all these may represent the reason why the OWS movement works as a profanation of current narratives, which tend to preach precisely the opposite. The more spaces for protest, dissent and resistance â indeed the more spaces of profanation â are nowadays created, the more the 'sacredness' of current institutions, their narratives and their vocabulary will be engaged and put in question, thus possibly overcome.